Trade in services in south Asia : opportunities and risks of liberalization - Kelegama, Saman, Ed (Sage Publications, 2009)
Revised version of papers presented at the International Conference on "Trade in Services in South Asia : Opportunities and Risks in Liberalization", held at Colombo during 4-5 April 2007.